Dental Management in a 7-year-old Child with Ichthyosis Vulgaris: A Rare Case Report - Divya Banu M; Krishna Priya Vellore; Santhosh K Challa; Niharika S (Journal of South Asian Association of Pediatric Dentistry)
Ichthyosis Vulgaris is a rare cornification disorder affecting the skin characterized by the accumulation of hyperkeratotic fish-like scales on the skin surface. It is a minor form of ichthyoses disorder. There is little evidence related to oral and dental manifestations in these patients. As their general manifestations can lead to oral and dental manifestations also, it is important to take various precautions by the dentists while managing these children. Also, preventive therapies can be initiated in them in the early stages to limit the acquired dental manifestations. This case reports various dental considerations and management carried out in a 7-year-old female patient who was a known case of Ichthyosis Vulgaris.